SwiftUI for dummies - Lee, Wei-Meng 1972- (John Wiley & Sons, Inc., 2020)
Have a unique app idea but worried you don't quite have the coding skills to build it? Good news: You can stop fretting about someone beating you to market with the same idea and start work right now using SwiftUI. SwiftUI is a gateway app development framework that has become one of the best ways for fledgling developers to get iOS apps off the ground without having to become a coding expert overnight. SwiftUI For Dummies makes that process even faster, providing a friendly introduction to the SwiftUI and Swift programming language and helping you feel right at home creating and building with playgrounds. The book also covers the frameworks and APIs that make it so easy to create smooth, intuitive interfaces--just dive right in and have fun!
Includes index
"Develop world-class applications for Apple devices. Create intuitive interfaces with SwiftUI. Learn the features of Swift programming"--Cover
Keywords: Application software / Development; Swift (Computer program language); User interfaces (Computer systems); iOS (Electronic resource)